Ancestry and TPMT-VNTR Polymorphism: Relationship with Hematological Toxicity in Uruguayan Patients with Acute Lymphoblastic Leukemia - Burgueño-Rodríguez, Gabriela; Méndez, Yessika; Olano, Natalia; Dabezies, Agustín; Bertoni, Bernardo; Souto, Jorge; Castillo, Luis; da Luz, Julio; Soler, Ana María (Frontiers in Pharmacology, 2020)
6-Mercaptopurine (6-MP) is a thiopurine drug widely used in childhood Acute Lymphoblastic Leukemia (ALL) therapy. Genes such as TPMT and NUDT15 have an outstanding role in 6-MP metabolism. Mutations in both genes explain a significant portion of hematological toxicities suffered by ALL Uruguayan pediatric patients. A variable number tandem repeat in TPMT promoter (TPMT-VNTR), has been associated with TPMT expression. This VNTR has a conservative architecture (AnBmC). To explore new causes of hematological toxicities related to ALL therapy, we genotyped the TPMT-VNTR of 130 Uruguayan pediatric patients. Additionally, individual genetic ancestry was estimated by 45 ancestry informative markers (AIMs). Hematological toxicity was measured as the number of leukopenia events and 6-MP dose along maintenance phase. As previously reported, we found TPMT*2 and TPMT*3C alleles associated to TPMT-VNTR A2BC and AB2C respectively. However, contrasting with other reports, TPMT*3A allele was found in a heterogeneous genetic background in linkage equilibrium. Patients carrying more than five A repeats present a significant higher number of leukopenia events among patients without TPMT and/or NUDT15 variants. Native American ancestry and the number of A repeats were significantly correlated with the number of leukopenia events. However, the correlation between Native American ancestry and the number of leukopenia events was lost when the number of A repeats was considered as covariate. This suggests that TPMT-VNTR alleles are more relevant than Native American ancestry in the hematological toxicity. Our results emphasize that TPMT-VNTR may be used as pharmacogenetic biomarker to predict 6-MP related hematological toxicity in ALL childhood therapy.